Hybrid optical communication systems leveraging orbital angular momentum multiplexing: multi-user access and performance analysis under diverse transmission scenarios - Singh, Mehtab; Abd El-Mottaleb, Somia A.; Alsharari, Meshari; Aliqab, Khaled; Armghan, Ammar (Frontiers in Physics, 2025)
This study proposes a new hybrid optical communication system that integrates free space optics (FSO) and single-mode fiber (SMF) links. This leverages orbital angular momentum (OAM) beam multiplexing to enable multi-user access across diverse geographical and channel conditions. Unlike prior studies that were constrained to homogeneous channels and identical user locations, the proposed system modulates four independent 10 Gbps OOK-NRZ data streams onto distinct OAM beams (ℓ = 0, 15, 40, 70), generated from a single 1,550 nm continuous wave (CW) laser. The heterogeneous transmission architecture comprises two OAM beams (ℓ = 40, 70) propagating through a clear-weather FSO channel (0.14 dB/km attenuation) and directly received, a third beam (ℓ = 15) transitioning from FSO to SMF, and a fourth beam (ℓ = 0) traversing a cascaded FSO link with a fog-affected secondary channel. System performance is rigorously evaluated using Bit Error Rate (BER), Q-factor, and eye diagrams. The results show that direct FSO reception achieves BER <10−6 over 10 km, while hybrid FSO/SMF transmission (ℓ = 15) maintains BERs of < 10−6, 10−4, and 10−3 for SMF lengths of 75 km under FSO divergence angles of 0.25 , 0.5 , and 0.25 mrad, respectively (fixed FSO range: 1 km). The fog-impacted cascaded FSO channel (ℓ = 0) sustains BERs of 10−5.7, 10−6.3, and 10−5.9 under low (LF: 9 dB/km), moderate (MF: 8 dB/km), and heavy fog (HF: 27 dB/km), demonstrating resilience in adverse conditions. By unifying OAM multiplexing with hybrid FSO/SMF infrastructure, this research advances scalable and reconfigurable optical networks for heterogeneous users in dynamic environments, with applications in last mile connectivity, backbone networks, and disaster-resilient communications.